2011
DOI: 10.1007/s10409-011-0439-7
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial fluid flow: simulation of mechanical environment of cells in the interosseous membrane

Abstract: In vitro experiments have shown that subtle fluid flow environment plays a significant role in living biological tissues, while there is no in vivo practical dynamical measurement of the interstitial fluid flow velocity. On the basis of a new finding that capillaries and collagen fibrils in the interosseous membrane form a parallel array, we set up a porous media model simulating the flow field with FLUENT software, studied the shear stress on interstitial cells' surface due to the interstitial fluid flow, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Actually, the smaller ϕ is, the greater effect on τ cell, max⁡ is. At normal physiological values, ϕ has much smaller effects than when the values are outside of the normal physiological range [19]. Increasing intravascular capillary pressure or capillary permeability can increase τ cell .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the smaller ϕ is, the greater effect on τ cell, max⁡ is. At normal physiological values, ϕ has much smaller effects than when the values are outside of the normal physiological range [19]. Increasing intravascular capillary pressure or capillary permeability can increase τ cell .…”
Section: Discussionmentioning
confidence: 99%
“…We proposed a dynamic model to simulate the interstitial fluid flow near meridians and discovered that the source of direct impetus for this flow was the penetration of plasma between capillaries and interstitial fluid [17]. Furthermore, we developed a two-dimensional (2D) model to study the flow field in connective tissues and observed directional fluid flow [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…In the context of acupuncture, the interstitial flow has been modeled by the Brinkman equations. The flow is driven by the difference in hydrostatic and osmotic pressures between the capillaries and the interstitial space [25,26].…”
Section: The Interstitial Fluidmentioning
confidence: 99%
“…11 We also simulate the subcutaneous interstitial flow under TCM treatment. 12,13 Pedersen et al simulated how the architecture of extracellular fibers affects the shear stress on cell membranes and found that interstitial fluid flow is important to the cell imbedded in a 3D matrix. 14 Their researches focused on the effects of interstitial fluid induced by acupuncture manipulation.…”
Section: Introductionmentioning
confidence: 99%